(untitled) (Research, Society and Development, 2022)
Polymers are increasingly present in everyday life to replace other materials. Because they are cheap and have attractive mechanical properties, they were and still are produced on a large scale and, consequently, their large volumes in landfills present a challenge for their recycling. Thus, the objective of this study was to evaluate the depolymerization of expanded polystyrene (EPS) waste through the use of microwaves using two agents that have carbon in their constitution to assist in depolymerization: graphene oxide (GO) and activated carbon (AC). Different amounts of GO and AC (0.125, 0.25, 0.5 g) were used, always keeping the mass of the EPS sample constant at 1 g. The tests in the microwave oven were performed in 3 cycles of 4 minutes each, with a total time of 12 minutes per batch. Inside the oven, the sample was placed inside a round-bottomed flask wrapped with rock wool. To characterize the material obtained from depolymerization, a mass balance was performed to evaluate the depolymerization yields associated with Fourier Transform Infrared Spectroscopy (FTIR) and thermogravimetric analysis (TGA). For the sample containing 0.125 g of GO, it was observed the formation of a larger solid fraction, little gaseous fraction and no liquid fraction. The sample with 0.25 g of GO showed the best yield of volatiles, with 22.58% of volatiles, and it was possible to observe both the liquid and the gaseous fractions. When AC catalyst was used the depolymerization extension was lower than GO. Samples containing with 0.125, 0.250 and 0.5 g of AC yielded gaseous fractions of 5.13; 9.16; and 3.06, respectively. In FTIR analysis it was not possible identify the formation of new bands for samples treated with GO or AC, when compared with EPS. Some new degradation peaks, when compared with EPS, were observed in TGA for samples that used GO as catalyst; which can be associated with the formation of more volatile compounds after depolymerization. The samples treated with AC showed a less pronounced reduction in its thermal stability. This study suggests that the heat transfer from the dark particle to the EPS sample is more effective when GO is used which may contribute to the depolymerization of EPS wastes.